Effect of cold atmospheric pressure plasma treatment on inactivation of Campylobacter jejuni on chicken skin and breast fillet. (May 2018) - Rossow, Marko; Ludewig, Martina; Braun, Peggy Gabriele
Abstract: The applicability of an atmospheric pressure plasma jet to reduce Campylobacter jejuni on chicken skin and breast fillet was evaluated. The efficacy of plasma treatment against two C. jejuni strains was examined using different feed gases (argon, air), exposure times (30–180 s) and distances from plasma source to sample (5, 8 or 12 mm). Furthermore, changes in color and temperature of treated samples were measured. Maximum mean C. jejuni reductions using argon or air as feed gases ranged from 0.78 to 2.55 and 0.65 to 1.42 log CFU/cm 2, respectively. Highest C. jejuni reductions were observed when using argon as feed gas, especially at longer treatment times. Most experimental settings had low and insignificant impact on color values. However, when using argon combined with a shorter distance of 8 mm, the lightness ( L *) of chicken breast samples increased significantly after 120 s treatment time. Temperature measurement revealed a maximum surface temperature of 61 °C, suggesting that denaturation could have affected inactivation efficacy and L* values. This study shows that C. jejuni can effectively be reduced on chicken skin and breast fillet using an atmospheric pressure plasma jet. Highlights: Significant reductions of C. jejuni on chicken skin and breast fillet using a plasma jet were shown. Best inactivation efficacy was observed using argon as feed gas at longer treatment times (≥120 s). Use of argon increased lightness of chicken breasts at 8 mm, but not at 12 mm treatment distance.